PENGARUH PEMBERIAN PEG 6000 TERHADAP DISOLUSI TABLET ASETOSAL DALAM SISTEM DISPERSI PADAT - Adi Fauzi; Desy Nawangsari; Galih Samodra (Jurnal Farmasi IKIFA, 2024)
Acetosal is included in class II non-steroidal anti-inflammatory drugs according to the Biopharmaceutical Classification System (BCS) which has low solubility and high permeability. Low solubility is an obstacle in drug release so it is necessary to develop active ingredients in increasing the dissolution rate. Polyethylene glycol 6000 is a water-soluble polymer and is most widely used in solid dispersion systems. This study aims to determine the effect of the addition of PEG 6000 on the dissolution rate of acetosal in a solid dispersion system. Solid dispersion using dissolution method with variation of acetosal concentration: PEG 6000 1:0, 1:1, 1:2, 1:3, 1:4 and 1:5. The best solid dispersion dissolution is found in the 1:3 ratio with a value of 98.87%. The results of the one way ANOVA test resulted in a significance value of 0.186 (p < 0.05) which indicates that there is no significant difference in dissolution rate due to the addition of PEG 6000 to the solid dispersion system formulation. The best dispersion formula results were made tablet preparations. The physical evaluation of tablets obtained results are weight uniformity test (mg) (641.4 ± 4.05), size uniformity test (cm) (diameter 1.19 ± 0.01 and thickness 0.409 ± 0.003), friability test (%) (0.23 ± 0.20), hardness test (kg) (4.5 ± 0.3), disintegration time test (minutes) (7.06 ± 1.04) and acetosal tablets dissolved 99.87% within 30 minutes. The conclusion of this study is that the addition of PEG 6000 in the solid dispersion system of acetosal tablets can increase the dissolution rate of acetosal tablets in solid dispersion systems and improve the physical properties of acetosal tablets.